Tailoring the Mechanical Properties of Metaluminous Aluminosilicate Glasses by Phosphate Incorporation - Grammes, Thilo; Limbach, René; Bruns, Sebastian; van Wüllen, Leo; de Ligny, Dominique; Kamitsos, Efstratios I.; Durst, Karsten; Wondraczek, Lothar; Brauer, Delia S. (Frontiers in Materials, 2020)
The characterization of aluminosilicate glasses is highly relevant in geosciences and for engineering applications such as reinforcement fibers or touchscreen covers. The incorporation of phosphate as a third network-forming species into these glasses offers unique opportunities for fine-tuning glass properties via changes in glass structure and polymerization. In this work, we studied melt-quenched aluminosilicate glasses within the system SiO2-Al2O3-Na2O-P2O5 with 50–70 mol% SiO2 and up to 7.5 mol% P2O5. All glasses were metaluminous (Al:Na = 1) in order to maximize the degree of polymerization. Increasing the phosphate content at the expense of NaAlO2 led to reduced glass polymerization and density, resulting in a decrease in elastic moduli and hardness and an increase in strain-rate sensitivity. When increasing the silica content by substituting SiO4 for AlO4 tetrahedra, network polymerization remained mostly unchanged, as confirmed by nearly constant hardness. Densification upon indentation was analyzed by Raman spectroscopy and finite element analysis. We find that the elastic properties and hardness of metaluminous phospho-aluminosilicate glasses are governed by changes in density and network polymerization. Other mechanical properties underlie more complex changes in glass structure.